Water Consumption Systems Assessment in Schools (in Lattakia Governorate) - جناد, هيثم; سلمان, هناء; ماشي, لمى (Latakia University Journal -Engineering Sciences Series, 2021)
The provision of safe drinking water is one of the most important challenges facing many countries, due to the lack of safe drinking water in the required quantity and quality, and the ease of exposure of water sources to different types of pollutants that cause the spread of intestinal diseases and infectious diseases. The research aims to estimate the water consumption rate in some educational establishments in Lattakia governorate and evaluating the viability of drinking water from the bacterial side and comparing it with the Syrian standard approved in this field. Periodic bacterial analyses of the main grid water were performed as well as the reservoir in 30 primary ,preparatory and secondary schools, were conducted and a survey of water consumption data was effected between 2013 and 2019, with the student's water consumption calculated daily. The bacterial analyzes of water in the main network feeding schools show that it meets Syrian drinking water standard but the residual free chlorine concentration measured was (0.1-0.5)mg/l so it lowest than the permissible limits (0.4-0.6)mg/l. There is also a bacterial contamination of the reservoir's water by 43% of schools and thus unusable water. With regard to water consumption, the statistical study of student water consumption data per day showed that 87.17% of the readings were below the minimum of 15-25 l/student.d according to UNICEF. This indicates that the water is insufficient in the quantity required.